Community acquired urinary tract infection: etiology and bacterial susceptibility - Dias Neto, José Anastácio (2003)
PURPOSE: Urinary tract infections (UTI) are one of the most common infectious diseases diagnosed. UTI account for a large proportion of antibacterial drug consumption and have large socio-economic impacts. Since the majority of the treatments begins or is done completely empirically, the knowledge of the organisms, their epidemiological characteristics and their antibacterial susceptibility that may vary with time is mandatory. OBJECTIVE: The aim of this study was to report the prevalence of uropathogens and their antibiotic susceptibility of the community acquired UTI diagnosed in our institution and to provide a national data. METHODS: We analyzed retrospectively the results of urine cultures of 402 patients that had community acquired urinary tract infection in the year of 2003. RESULTS: The mean age of the patients in this study was 45.34 ± 23.56 (SD) years. There were 242 (60.2%) females and 160 (39.8%) males. The most commonly isolated organism was Escherichia coli (58%). Klebsiella sp. (8.4%) and Enterococcus sp.(7.9%) were reported as the next most common organisms. Of all bacteria isolated from community acquired UTI, only 37% were sensitive to ampicillin, 51% to cefalothin and 52% to trimethoprim/sulfamethoxazole. The highest levels of susceptibility were to imipenem (96%), ceftriaxone (90%), amikacin (90%), gentamicin (88%), levofloxacin (86%), ciprofloxacin (73%), nitrofurantoin (77%) and norfloxacin (75%). CONCLUSION: Gram-negative agents are the most common cause of UTI. Fluoroquinolones remains the choice among the orally administered antibiotics, followed by nitrofurantoin, second and third generation cephalosporins. For severe disease that require parenteral antibiotics the choice should be aminoglycosides, third generation cephalosporins, fluoroquinolones or imipenem, which were the most effective.